If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + -3) = -2 Reorder the terms: (-3 + x) = -2 Remove parenthesis around (-3 + x) -3 + x = -2 Solving -3 + x = -2 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + x = -2 + 3 Combine like terms: -3 + 3 = 0 0 + x = -2 + 3 x = -2 + 3 Combine like terms: -2 + 3 = 1 x = 1 Simplifying x = 1
| 20x^3-20x=0 | | 4(6x+2)=56 | | 3x-4=4x-17 | | k^2-3k+5=0 | | 4y-7=2(y+1) | | F=1.8(37)+32 | | 5y-20=10 | | 12x^5+15x+9=0 | | -x^2+15x+54=0 | | K=10+273 | | 2x+6=-26-6x | | 4y-1=2y+2 | | X^2=3(5x+18) | | 5x+5-2x=29 | | 9+6x=x+59 | | (3x-2)(x-2)=4x-36 | | 20y-16=18-9 | | K=40+273 | | 4(3a-2)+3a=19 | | F=1.8(40)+32 | | 7x-10=114-6x | | 305=5x^3 | | K=30+273 | | -6+7x=x-12 | | 3(2x+5)=11-4x | | 6y(4y-3)+15y= | | 15x+5=80 | | 5-2(-3/5)=3(-3/5)+8 | | 4-2(x+5)=9 | | F=1.8(30)+32 | | 3x-6x^2=0 | | 7-x-6x=-28 |